Development mechanical and fatigue properties of AA7001 after combined SP with deep cryogenic treatment and UIP with deep cryogenic treatment - Alhamdany, Aseel A.; Khenyab, Ali Yousuf; Mohammed, Qusay K.; Alalkawi, Hussain Jasim M. (Eastern-European Journal of Enterprise Technologies, 2021)
Al alloys have long been of interest to the aerospace community, due to their modest specific strength, ease of manufacture, and low cost. In recent years, with the rapid development of weaponry, 7XXX ultra-high strength aluminum alloys used increasingly in military ﬁelds. Chemical analysis of the AA 7001 is supported out at The Company State for Engineering, Rehabilitation and Inspection (SIER) in Iraq. Strengthening the surface (shot penning) is beneficial to delay crack nucleation and extend life. The test samples (tensile and fatigue) are subject to the SP process by using ball steel with the parameters (Pressure=12 bars, Speed=40 mm/min, Distance=150 mm, Shot size=2.25 mm, Coverage=100 %). The ultrasonic impact treatment (UIP) machine is used for enhancing the surface properties. For the Deep Cryogenic Treatment (DCT), the samples have been placed in the cooling chamber. A standard tensile test specimen is prepared in a round section with the dimensions chosen according to ASTM (A370-11). Tensile and fatigue of rotating bending with R=–1 have been conducting, after the effect of deep cryogenic treatment (DCT), combined shot peening (SP+DCT), and ultrasonic impact peening (UIP+DCT) of AA7001 have been examining. The maximum improvement percent in ultimate tensile strength (UTS) due to (DCT), (SP+DCT), and (UIP+DCT) were about 3 %, 8.27 %, and 6.25 %, respectively. The rise in the yield stress due to (DCT), (SP+DCT), and (UIP+DCT) were 9.5 %, 14.6 %, and 13.14 %, respectively. The ductility reduced by constituents of 8.57 %, 12.5 %, and 11.42 % sequentially. The improvement in fatigue strength in a high cycle regime is 16 % for (SP+DCT) due to combined effects, it is an 8 % increase in the endurance limit on fatigue behavior due to inducing compressive residual stress (CRS)